Differential cellular responses associated with oxidative stress and cell fate decision under nitrate and phosphate limitations in Thalassiosira pseudonana: Comparative proteomics. - Qun Lin; Jun-Rong Liang; Qian-Qian Huang; Chun-Shan Luo; Donald M Anderson; Chris Bowler; Chang-Ping Chen; Xue-Song Li; Ya-Hui Gao (PLoS ONE)
Diatoms are important components of marine ecosystems and contribute greatly to the world's primary production. Despite their important roles in ecosystems, the molecular basis of how diatoms cope with oxidative stress caused by nutrient fluctuations remains largely unknown. Here, an isobaric tags for relative and absolute quantitation (iTRAQ) proteomic method was coupled with a series of physiological and biochemical techniques to explore oxidative stress- and cell fate decision-related cellular and metabolic responses of the diatom Thalassiosira pseudonana to nitrate (N) and inorganic phosphate (P) stresses. A total of 1151 proteins were detected; 122 and 56 were significantly differentially expressed from control under N- and P-limited conditions, respectively. In N-limited cells, responsive proteins were related to reactive oxygen species (ROS) accumulation, oxidative stress responses and cell death, corresponding to a significant decrease in photosynthetic efficiency, marked intracellular ROS accumulation, and caspase-mediated programmed cell death activation. None of these responses were identified in P-limited cells; however, a significant up-regulation of alkaline phosphatase proteins was observed, which could be the major contributor for P-limited cells to cope with ambient P deficiency. These findings demonstrate that fundamentally different metabolic responses and cellular regulations are employed by the diatom in response to different nutrient stresses and to keep the cells viable.